Thermodynamic analysis of the quantum critical behavior of Ce-lattice compounds - Sereni, J.G. (2012)
Fil: Sereni, J. G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina